2013
DOI: 10.1103/physrevd.87.014503
|View full text |Cite
|
Sign up to set email alerts
|

Resonance parameters of the rho-meson from asymmetrical lattices

Abstract: We present a lattice QCD calculation of the parameters of the ρ meson decay. The study is carried out on spatially asymmetric boxes using nHYP-smeared clover fermions with two mass-degenerate quark flavors. Our calculations are carried out at a pion mass mπ = 304(2) MeV on the set of lattices V = 24 2 × η24 × 48 with η = 1.0, 1.25, and 2.0 with lattice spacing a = 0.1255(7) fm. The resonance mass mρ = 827(3)(5) MeV and coupling constant gρππ = 6.67(42) are calculated using the P-wave scattering phase shifts. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 29 publications
5
145
0
Order By: Relevance
“…In particular, the Lüscher method and its extensions for relating finite-volume spectra to scattering amplitudes are now well established for elastic [5][6][7][8][9][10][11][12][13][14] and coupled-channel [15][16][17][18][19] hadron-hadron scattering. These methods have been demonstrated in a number of applications, notably for the ρ-resonance seen in P -wave ππ scattering [20][21][22][23][24][25][26][27][28][29], and for the σ resonance seen in S-wave ππ scattering [30]. It has also recently been shown that, with sufficiently extensive and precise spectra, information on coupled-channel hadron-hadron scattering amplitudes can be obtained [26,[31][32][33] -this is crucial for understanding highly excited states that are typically kinematically permitted to decay into several channels.…”
Section: Jhep10(2016)011mentioning
confidence: 99%
“…In particular, the Lüscher method and its extensions for relating finite-volume spectra to scattering amplitudes are now well established for elastic [5][6][7][8][9][10][11][12][13][14] and coupled-channel [15][16][17][18][19] hadron-hadron scattering. These methods have been demonstrated in a number of applications, notably for the ρ-resonance seen in P -wave ππ scattering [20][21][22][23][24][25][26][27][28][29], and for the σ resonance seen in S-wave ππ scattering [30]. It has also recently been shown that, with sufficiently extensive and precise spectra, information on coupled-channel hadron-hadron scattering amplitudes can be obtained [26,[31][32][33] -this is crucial for understanding highly excited states that are typically kinematically permitted to decay into several channels.…”
Section: Jhep10(2016)011mentioning
confidence: 99%
“…The ρ mass in table 2 was extracted as m ρ = E ρ (p = 0) in [3] and is indeed found close to m res ρ in all simulations [1][2][3][4][5][6]. The ω energy is calculated using quark-antiquark interpolators O s=n 1−5 given by eq.…”
Section: Masses Of π ρ ωmentioning
confidence: 99%
“…This is the case also for all vector (J P = 1 − ) and axial-vector (J P = 1 + ) mesons. The vector resonance ρ is the only hadronic resonance that has been treated on the lattice by several collaborations [1][2][3][4][5][6], taking into account its unstable nature and extracting its resonance mass as well as the width. First steps in this direction were also made recently for the vector resonance K * (892) [7], where mass and width were extracted.…”
Section: Introductionmentioning
confidence: 99%
“…If the resonance is sufficiently far away from thresholds and in the absence of background, a simple Breit-Wigner parameterization allows to describe the phase shift and to determine the width. The prime examples are given by the ρ(770) [8][9][10][11][12][13] and also the K * (892) [14,15]. A first πK − ηK coupled-channel analysis has been carried out recently [16], see also Ref.…”
Section: Introductionmentioning
confidence: 99%